2014
DOI: 10.11604/pamj.2014.19.349.5090
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement in family planning decision making in sub-Saharan Africa- what the evidence suggests

Abstract: The World Health Organization (WHO) estimated in 2012 that 287,000 maternal deaths occurred in 2010; sub-Saharan Africa (56%) and Southern Asia (29%) accounted for the global burden of maternal deaths. Men are also recognized to be responsible for the large proportion of ill reproductive health suffered by their female partners. Male involvement helps not only in accepting a contraceptive but also in its effective use and continuation. The objectives were to assess men's knowledge, attitude, and practice of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(179 citation statements)
references
References 11 publications
11
165
0
3
Order By: Relevance
“…Male approval of family planning has been associated with increased male involvement 32 . Male involvement has been promoted in many quarters as a key to increasing contraceptive prevalence and has been called into question by others 1,[33][34][35] . Our study had some limitations.…”
Section: African Journal Of Reproductive Health June 2017; 21 (2)mentioning
confidence: 99%
“…Male approval of family planning has been associated with increased male involvement 32 . Male involvement has been promoted in many quarters as a key to increasing contraceptive prevalence and has been called into question by others 1,[33][34][35] . Our study had some limitations.…”
Section: African Journal Of Reproductive Health June 2017; 21 (2)mentioning
confidence: 99%
“…However, family planning services traditionally targeted women regardless of the fact that men's involvement is equally important and childbearing has an impact on men's life too. A review of male involvement in decision making in family planning in Sub-Saharan Africa reflected low involvement of men in family planning programs [5]. A research report from Muslim communities in Ghana suggested further low male involvement in family planning uptake and higher non- Tamiso) 47 approval of for spouses contrary to perfect knowledge and awareness to contraceptive options [6].…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding has been reported in developing countries particularly in Sub-Saharan African. Vouking (2014);Okigbo et al (2013);Odu et al (2005) reported in their studies that men who solely take a decision on household earnings were more likely to want more children than men whose wives solely take a decision on household earnings. This finding may be due to dominating of men in reproductive decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, limited studies have delved into men's decision-making role in affecting contraceptive use, as a means of controlling fertility in Nigeria. Studies in sub-Saharan Africa have shown that male partners have absolute decision-making power that brings about the compliance and submission of their wives (Vouking, 2014). For instance, a study carried out among Mozambique women showed that husband influenced a woman's intention to use contraceptives (Mboane and Bhatta, 2015).…”
Section: Introductionmentioning
confidence: 99%